Question and Answers Forum

All Questions      Topic List

Others Questions

Previous in All Question      Next in All Question      

Previous in Others      Next in Others      

Question Number 39586 by Rio Mike last updated on 08/Jul/18

show that   a) ((1 + 2sin2θ − cos2θ)/(1+sin2θ + cos 2θ)) = tan θ  b) tan^2 A − tan^2 B = ((sin^2 A−sin^2 B)/(cos^2 A cos^2 B))

showthata)1+2sin2θcos2θ1+sin2θ+cos2θ=tanθb)tan2Atan2B=sin2Asin2Bcos2Acos2B

Answered by Joel579 last updated on 08/Jul/18

LHS  ((1 + sin 2θ − cos 2θ)/(1 + sin 2θ + cos 2θ))  = (((sin^2  θ + cos^2  θ) + sin 2θ − (cos^2  θ − sin^2  θ))/((sin^2  θ + cos^2  θ) + sin 2θ + (cos^2  θ − sin^2  θ)))  = ((2sin^2  θ + 2 sin θ cos θ )/(2cos^2  θ + 2 sin θ cos θ))  = ((2sin θ(sin θ + cos θ))/(2cos θ(cos θ + sin θ)))  = tan θ  →  RHS

LHS1+sin2θcos2θ1+sin2θ+cos2θ=(sin2θ+cos2θ)+sin2θ(cos2θsin2θ)(sin2θ+cos2θ)+sin2θ+(cos2θsin2θ)=2sin2θ+2sinθcosθ2cos2θ+2sinθcosθ=2sinθ(sinθ+cosθ)2cosθ(cosθ+sinθ)=tanθRHS

Answered by Joel579 last updated on 08/Jul/18

LHS   tan^2  A − tan^2  B  = ((tan^2  A − tan^2  B(cos^2  A cos^2  B))/(cos^2  A cos^2  B))  = ((sin^2  A cos^2  B − sin^2  B cos^2  A)/(cos^2  A cos^2  B))

LHStan2Atan2B=tan2Atan2B(cos2Acos2B)cos2Acos2B=sin2Acos2Bsin2Bcos2Acos2Acos2B

Terms of Service

Privacy Policy

Contact: info@tinkutara.com